Ovid’s Heroides: fluctuations among drama, lyrics and epos - Ulčinaitė, Eugenija (Literatūra, 2008)
Ovid’s Heroides is one of the most enigmatic oeuvres written by the famous poet. Heroides still continues to raise many questions to which the answers have not been discovered yet. For example, it is not clear when the oeuvre was written; the genre itself still remains puzzling. Some researchers consider Heroides to illustrate the continuation of the elegiac verse, while others link this oeuvre with the tradition of the literary letter. Still others discern in this oeuvre the influence produced by the Hellenistic Greek poetry, and even that effected by the novel.Heroides consists of twenty one letters, written in the metre of elegiac distich. The work is based on the mythological plots, borrowed from Homer’s Odyssey and Iliad, as well as on those taken from the plays by Aeschylus, Sophocles, and Euripides. Vergil’s Aeneid alongside with the poetry written by Catullus, Apollonius Rhodius and Callimachus have left their imprint on this oeuvre by Ovid as well.All the letters written by the women in this oeuvre reverberate their enormous emotional tension. Their husbands or lovers are gone away and have not returned for a long time. The women are waiting for their men, who, unfortunately, do not seem to be conscious of the feelings of the women or simply do not respond. Irrespective of the fact that the motivation behind all the letter writing seems to be similar, the poetical and emotional expressions of these letters are neither monotonous nor tedious. The letters embrace a vast range of feelings and emotions.In the recent analyses of Ovid’s Letters, the psychological character of these letters as well as the poet’s mastery in reflecting the feelings of the women are emphasized by the latest researchers. Ovid’s Letters abound in dramatic, lyrical and epic means of expression.